2005
DOI: 10.1212/01.wnl.0000188871.74093.12
|View full text |Cite
|
Sign up to set email alerts
|

APOE alleles predict the rate of cognitive decline in Alzheimer disease

Abstract: APOE genotype strongly predicts the rate of cognitive decline in Alzheimer disease. The decline shows a dose-response relation with the APOE epsilon4 allele, but the APOE epsilon2 allele is protective. The nonlinear model yielded larger estimates of the maximal rate of decline than the linear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
163
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(188 citation statements)
references
References 54 publications
(89 reference statements)
14
163
1
10
Order By: Relevance
“…Further, a meta‐analysis of 1063 APOEε4 carriers and 2983 non‐carriers 32 found no association of APOEε4 with increased cognitive decline at 1 year after surgery (OR 1.15, 95% CI 0.71–1.86). However, APOEε4 has been shown to accelerate cognitive decline in elderly people, whether non‐demented 25 or with Alzheimer's disease 24, regardless of surgery. Thus, elderly cognitively impaired, APOEε4 carriers who experience moderate or major surgery may be in danger of suffering particularly rapid cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a meta‐analysis of 1063 APOEε4 carriers and 2983 non‐carriers 32 found no association of APOEε4 with increased cognitive decline at 1 year after surgery (OR 1.15, 95% CI 0.71–1.86). However, APOEε4 has been shown to accelerate cognitive decline in elderly people, whether non‐demented 25 or with Alzheimer's disease 24, regardless of surgery. Thus, elderly cognitively impaired, APOEε4 carriers who experience moderate or major surgery may be in danger of suffering particularly rapid cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were seen at least annually, at many of which visits a Cambridge Cognition Examination (CAMCOG) score (variable termed ‘C’ below) was obtained 23 and details of episodes of surgery since the preceding assessment recorded. Patients were genotyped with regard to the APOEε4 allele, which is known to be associated with a greater risk of cognitive decline 24, 25 and diagnosis of Alzheimer's dementia 26. We sought participants with at least two measures of CAMCOG who had joined the study as controls, or with mild cognitive impairment 27, who had participated in at least 3 years of follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…AD begins with subtle changes in synaptic efficacy well before neuronal degeneration is apparent, and loss of synapses likely disrupts hippocampal and cortical circuits, with functional consequences contributing to progressive cognitive impairment [28][29][30]. Even in non-demented middle-aged and elderly human subjects, apoE4 is associated with greater cognitive decline, and the decline shows a gene doseresponse [31][32][33]. A significant association was found between apoE4 and transition from normal to mild cognitive impairment [34], which represents early-stage AD and with high positive predictive value for eventual conversion to AD [35].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The literature is conflicting as to the effect of e4 on rate of cognitive decline; some studies show slower [4][5][6] whereas others faster rates. [7][8][9][10][11] This discrepancy may reflect chance findings because of a lack of power in smaller studies. Studies with over 200 AD subjects have consistently shown a more aggressive course of disease with the e4 allele, 7,8,10 and in the PROSPER trial (a large prospective study in the elderly with 5804 subjects) the e4 allele was associated both with poorer memory performance at baseline and with more rapid cognitive decline.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] This discrepancy may reflect chance findings because of a lack of power in smaller studies. Studies with over 200 AD subjects have consistently shown a more aggressive course of disease with the e4 allele, 7,8,10 and in the PROSPER trial (a large prospective study in the elderly with 5804 subjects) the e4 allele was associated both with poorer memory performance at baseline and with more rapid cognitive decline. 11 Nonetheless, smaller studies have generated some striking findings.…”
mentioning
confidence: 99%